Үйлээс үйл үг бүтээх дагаврын байрлалын тогтолцоо - Ж., Ганбаатар (Mongolian Studies, 2023)
The paper deals with the distribution of verb formation suffixes from verb and analyzes them in terms of their forward and backward relation to other suffixes in word structure based on some examples. In Mongolian, the occurence in which suffixes of the same parts of speech exist in a sequence of a word structure is uncommon than the occurence in which suffixes of different parts of speech are in the sequence of the word structure.